Lysine‐Targeting Covalent Inhibitors. Issue 48 (27th October 2017) - Pettinger, Jonathan; Jones, Keith; Cheeseman, Matthew D.
Abstract: Targeted covalent inhibitors have gained widespread attention in drug discovery as a validated method to circumvent acquired resistance in oncology. This strategy exploits small‐molecule/protein crystal structures to design tightly binding ligands with appropriately positioned electrophilic warheads. Whilst most focus has been on targeting binding‐site cysteine residues, targeting nucleophilic lysine residues can also represent a viable approach to irreversible inhibition. However, owing to the basicity of the ϵ ‐amino group in lysine, this strategy generates a number of specific challenges. Herein, we review the key principles for inhibitor design, give historical examples, and present recent developments that demonstrate the potential of lysine targeting for future drug discovery. Abstract : Target acquired : Targeted covalent inhibitors have gained widespread attention in drug discovery. Whilst the focus has been on targeting binding‐site cysteine residues, targeting nucleophilic lysine residues can also be a viable approach, although this strategy generates unique challenges. This Minireview summarizes the key principles, gives historical examples, and presents recent developments that demonstrate the potential of this approach for future drug discovery.